Synthesizing and databasing fossil calibrations: Divergence dating and beyond - Ksepka, Daniel T.; Benton, Michael J.; Carrano, Matthew T.; Gandolfo, Maria A.; Head, Jason J.; Hermsen, Elizabeth J.; Joyce, Walter G.; Lamm, Kristin S.; Patane, Jose S. L.; Phillips, Matthew J.; Polly, P. David; Van Tuinen, Marcel; et al. (Biology Letters, 2011)
Divergence dating studies, which combine temporal data from the fossil record with branch length data from molecular phylogenetic trees, represent a rapidly expanding approach to understanding the history of life. National Evolutionary Synthesis Center hosted the first Fossil Calibrations Working Group (3-6 March, 2011, Durham,NC, USA), bringing together palaeontologists, molecular evolutionists and bioinformatics experts to present perspectives from disciplines that generate, model and use fossil calibration data. Presentations and discussions focused on channels for interdisciplinary collaboration, best practices for justifying, reporting and using fossil calibrations and roadblocks to synthesis of palaeontological and molecular data. Bioinformatics solutions were proposed, with the primary objective being a new database for vetted fossil calibrations with linkages to existing resources, targeted for a 2012 launch. © 2011 The Royal Society.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Bioinformatics; Database; Molecular clocks; Palaeontology